Sustainable business performance of small and medium-sized enterprises in green hotels: the mediating role of competitive advantage - Ai Na Seow; Man Seong Chan; Chi Hau Tan; Yee-Yann Yap (Cogent Business & Management)
As environmental consciousness continues to gain attention, the hospitality industry is beginning to recognize the importance of incorporating green practices into its business operations. This study aims to comprehend the relationship between strategy agility, digital capability, open innovation, and entrepreneurial competency concerning small and medium-sized enterprises (SMEs)’ sustainable competitive advantage and sustainable business performance in the green hospitality industry. Data were collected from the management of SMEs with green practices (N = 288) using quantitative methods, and hypothesis analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that only open innovation and entrepreneurial competency have a positive impact on sustainable competitive advantage. Similarly, a sustainable competitive advantage has a positive impact on sustainable business performance. Further, sustainable competitive advantage mediates the relationship between open innovation, entrepreneurial competency, and sustainable business performance. The findings contribute to a deeper understanding of SMEs in the green hotel sector, highlighting the importance of sustainability in the hospitality industry. This research contributes practical value to the literature on utilizing green concepts to achieve sustainable competitive advantage and business performance in the service industry.